Anti-oxidative effects of the biennial flower of Panax notoginseng against H2O2-induced cytotoxicity in cultured PC12 cells - Chen Jijun; Dong Tina; Fu Qiang; Lau David; Cheung Anna; Xie Heidi; Jiang Zhiyong; Choi Roy; Wang Zhengtao; Tsim Karl (BMC, 2010)
Abstract Background Radix notoginseng is used in Chinese medicine to improve blood circulation and clotting; however, the pharmacological activities of other parts of Panax notoginseng have yet to be explored. The present study reports the anti-oxidative effects of various parts of Panax notoginseng. Methods Various parts of Panax notoginseng, including the biennial flower, stem-leaf, root-rhizome, fiber root and sideslip, were used to prepare extracts and analyzed for their anti-oxidation effects, namely suppressing xanthine oxidase activity, H2O2-induced cytotoxicity and H2O2-induced ROS formation. Results Among various parts of the herb (biennial flower, stem-leaf, root-rhizome, fiber root and sideslip), the water extract of the biennial flower showed the strongest effects in (i) inhibiting the enzymatic activity of xanthine oxidase and (ii) protecting neuronal PC12 cells against H2O2-induced cytotoxicity. Only the water extracts demonstrated such anti-oxidative effects while the ethanol extracts did not exert significant effects in suppressing xanthine oxidase and H2O2-induced neuronal cytotoxicity. Conclusions The present study demonstrates the biennial flower of Panax notoginseng to have neuroprotection effect on cultured neurons and the underlying protection mechanism may involve anti-oxidation.